An integrative review of the vigilance-avoidance model in pediatric anxiety disorders: Are we looking in the wrong place?. (May 2019) - Rosen, Dana; Price, Rebecca B.; Silk, Jennifer S.
Highlights: Vigilance-avoidance attention pattern is thought to contribute to anxiety in youth. We conducted a review to examine if the vigilance-avoidance model is supported. Overall, there was not support for the vigilance-avoidance model in anxious youth. Future attention bias research should use tasks that assess attention across time. Abstract: Enduring cognitive models of anxiety posit that negative biases in information processing are implicated in the etiology, maintenance, and recurrence of anxiety disorders in youth and adults. Specifically, the vigilance-avoidance model of attention is an influential hypothesis proposed to explain anxious individuals' attentional patterns. The vigilance-avoidance model posits that anxious individuals, relative to nonanxious individuals, initially orient more quickly to threatening stimuli and then later avoid threatening stimuli. However, a large body of empirical research examining attentional mechanisms in anxious individuals uses paradigms that do not allow the measurement of the time course of attention. Furthermore, existing reviews that examine the time course of attention only include studies with adults. We systematically review in depth the literature that compares anxious and non-anxious children that takes advantage of research designs that allow the examination of the time course of attention. Across studies, there is not robust support for the vigilance-avoidance model in samples of anxious youth. Future research examining attention biases across time should employ tasks that more directly measure multiple stages of attention, in order to assess if vigilance-avoidance patterns emerge based on sample characteristics or task variables, and to inform intervention efforts.